Adaptive attunement of selective covert attention to evolutionary-relevant emotional visual scenes - Fernández-Martín, Andrés; Gutiérrez-García, Aida; Capafons, Juan; Calvo, Manuel G (Consciousness and Cognition, 2017)
We investigated selective attention to emotional scenes in peripheral vision, as a function of adaptive relevance of scene affective content for male and female observers. Pairs of emotional neutral images appeared peripherally with perceptual stimulus differences controlled while viewers were fixating on a different stimulus in central vision. Early selective orienting was assessed by the probability of directing the first fixation towards either scene, and the time until first fixation. Emotional scenes selectively captured covert attention even when they were task irrelevant, thus revealing involuntary, automatic processing. Sex of observers and specific emotional scene content (e.g., male-to-female-aggression, families and babies, etc.) interactively modulated covert attention, depending on adaptive priorities and goals for each sex, both for pleasant and unpleasant content. The attentional system exhibits domain-specific and sex-specific biases and attunements, probably rooted in evolutionary pressures to enhance reproductive and protective success. Emotional cues selectively capture covert attention based on their bio-social significance.
Keywords: emotion; selective attention; eye movements; sex differences; visual scenes; JCR; Scopus